DARK MACHINES how artificial intelligence, digitalization and automation is changing our... living planet. - Galaz, Victor ([S.l.] : ROUTLEDGE, 2025)
This book offers a critical primer on how Artificial Intelligence and digitalization are shaping our planet and the risks posed to society and environmental sustainability. As the pressure of human activities accelerates on Earth, so too does the hope that digital and artificially intelligent technologies will be able to help us deal with dangerous climate and environmental change. Technology giants, international think-tanks and policy-makers are increasingly keen to advance agendas that contribute to AI for Good or AI for the Planet." Dark Machines explores why it is nave and dangerous to assume converging forces of a growing climate crisis and technological change will act synergistically to the benefit of people and the planet. It explores why AI and associated digital technologies may lead to accelerated discrimination, automated inequality, and augmented diffusion of misinformation, while simultaneously amplifying risks for people and the planet. We face a profound challenge. We can either allow AI accelerate the loss of resilience of people and our planet, or we can decide to act forcefully in ways that redirects its destructive direction. This urgent book will be of interest to students and researchers with an interest in Artificial Intelligence, digitalization and automation, social and political dimensions of science and technology, and sustainability sciences.
Keywords: Artificial intelligence -- Social aspects; Science -- Social aspects; Technology -- Social aspects; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / International Relations / General